Nonpharmacological Interventions in Targeting Pain-Related Brain Plasticity - Maral Tajerian; J. David Clark (Neural Plasticity)
Chronic pain is a highly prevalent and debilitating condition that is frequently associated with multiple comorbid psychiatric conditions and functional, biochemical, and anatomical alterations in various brain centers. Due to its widespread and diverse manifestations, chronic pain is often resistant to classical pharmacological treatment paradigms, prompting the search for alternative treatment approaches that are safe and efficacious. The current review will focus on the following themes: attentional and cognitive interventions, the role of global environmental factors, and the effects of exercise and physical rehabilitation in both chronic pain patients and preclinical pain models. The manuscript will discuss not only the analgesic efficacy of these therapies, but also their ability to reverse pain-related brain neuroplasticity. Finally, we will discuss the potential mechanisms of action for each of the interventions.